2016
DOI: 10.1016/j.biotechadv.2015.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Algae–bacteria interactions: Evolution, ecology and emerging applications

Abstract: Algae and bacteria have coexisted ever since the early stages of evolution. This coevolution has revolutionized life on earth in many aspects. Algae and bacteria together influence ecosystems as varied as deep seas to lichens and represent all conceivable modes of interactions - from mutualism to parasitism. Several studies have shown that algae and bacteria synergistically affect each other's physiology and metabolism, a classic case being algae-roseobacter interaction. These interactions are ubiquitous and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
487
0
9

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 990 publications
(501 citation statements)
references
References 226 publications
5
487
0
9
Order By: Relevance
“…Recent investigations into nutrient-removal pathways have provided the necessary knowledge for understanding nutrient removal by assimilation, anaerobic ammonia oxidation, nitrification and denitrification (Renuka et al, 2013;van Kessel et al, 2015;Santoro, 2016). Understanding of the complex interactions between attached microalgae and bacteria is pointing out how cooperative interactions allow for functionally stable consortium (Borowitzka, 2016;Ramanan et al, 2016). Besides, the increasing implementation of photobioreactors using attached microalgaebacteria consortium, such as Algal Turf Scrubbers (ATS) (Adey et al, 2013), tank photobioreactors (Su et al, 2011) and tubular biofilm photobioreactor (De Godos et al, 2009), are delivering valuable information about nutrient removal at low concentrations.…”
Section: Conventional Technologies Disadvantages Referencesmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent investigations into nutrient-removal pathways have provided the necessary knowledge for understanding nutrient removal by assimilation, anaerobic ammonia oxidation, nitrification and denitrification (Renuka et al, 2013;van Kessel et al, 2015;Santoro, 2016). Understanding of the complex interactions between attached microalgae and bacteria is pointing out how cooperative interactions allow for functionally stable consortium (Borowitzka, 2016;Ramanan et al, 2016). Besides, the increasing implementation of photobioreactors using attached microalgaebacteria consortium, such as Algal Turf Scrubbers (ATS) (Adey et al, 2013), tank photobioreactors (Su et al, 2011) and tubular biofilm photobioreactor (De Godos et al, 2009), are delivering valuable information about nutrient removal at low concentrations.…”
Section: Conventional Technologies Disadvantages Referencesmentioning
confidence: 99%
“…Meanwhile, bacteria decompose organic matter into mineral form and secrete extracellular metabolites such as auxins and vitamin B 12 , which are essential for microalgal growth (Fig. 2a) (Ramanan et al, 2016). Roeselers et al (2007) reported that substrate precolonization by Betaproteobacteria accelerated the growth and adhesion of Microcoleus vaginatus to polycarbonate surfaces.…”
Section: Cooperative Interactionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the Roseobacter -algae interaction is well known in marine ecosystems (Geng and Belas, 2010). Members of the Rhodobacteraceae (alphaproteobacteria) play an important role in carbon and sulphur biogeochemical cycle and are known to have a mutualistic interaction with different species of microalgae (Geng and Belas, 2010;González et al, 2000;Ramanan et al, 2016). This positive effect driven by the high bacterial biomass might also be due to the release of trace elements, such as a growth promoting factor, the hormone indole-3-acetic acid (de-Bashan et al, 2008), or by production of vitamins (Amin et al, 2012).…”
Section: Effect Of Bacteria On Diatom's Growth and Biochemical Composmentioning
confidence: 99%
“…Complex relationships exist between these two organisms for both growth and carbon flux, bacteria can enhance EPS excretion by microalgae and/or fed on the excreted carbon (Amin et al, 2012;Ramanan et al 2016). Previous studies on the diatom T. weissflogii found variable results on transparent exopolymer particles (TEP) secretion related to the bacterial community associated to the algae (Crocker and Passow, 1995;Passow, 2002).…”
Section: Effect Of Bacteria On Diatom's Growth and Biochemical Composmentioning
confidence: 99%